Fundamental Dan Implementasi Big Data Dalam Transformasi Digital - Haykal Tito Setiawan; Angga Reksa; Rizky Pratama Ramadani Ritonga; Sahat Parulian Sitorus (Universitas Labuhanbatu, 2026)
Digital transformation has encouraged organizations to optimally utilize information technology to manage data. Big data has become a key element that plays a crucial role in supporting the digitalization process in various sectors. The theoretical basis of this study discusses the concepts of big data, digital transformation, information systems, data governance, and digital human resources. These theories form the basis for understanding the relationship between technology and organizational performance. The research method used is descriptive qualitative, using a literature review and case study approach. Data was obtained from various reliable sources and systematically analyzed to obtain valid results. The results show that implementing big data can improve operational efficiency and the quality of decision-making. In addition, big data also drives innovation and strengthens organizational competitiveness. The research discussion emphasizes that the success of big data implementation is influenced by the readiness of human resources, infrastructure, and management support. A holistic approach is necessary for digital transformation to be sustainable. The study concludes that big data is a strategic asset in the digital era. Optimal utilization of big data can support organizational growth, innovation, and sustainability in the future.